The creation of new aneuploid lines of the cotton (Gossypium hirsutum L.) with identification of chromosomes by translocation and SSR-markers - M. F. Sanamyan; Sh. U. Bobokhujaev; A. X. Makamov; S. G. Achilov; I. Y. Abdurakhmonov (Вавиловский журнал генетики и селекции)
The use of monosomic lines significantly increases the effectiveness of molecular-genetic analysis and the development of superior quality breeding lines via substitutions by alien chromosomes. A complete set of aneuploid series for each cotton chromosome was required. Simple sequence repeats (SSR) have been applied as useful markers for understanding cotton genetics. Several DNA markers have already been assigned to the individual chromosomes of Gossypium hirsutum. The primary objective of this paper is to report the creation of new monosomic lines and the use of chromosome specific simple sequence repeat (SSR) markers and translocation lines for chromosome identification to confirm chromosome specificity of monosomic lines in the Uzbek collection. Here, we summarize data on the development of a monosomic stock collection of cotton (G. hirsutum L.) from Uzbekistan, including the origin of 95 primary monosomics, their cytogenetic characteristics, morphological features and their identification by translocation tests and chromosome SSR-markers. Our results indicated several different monosomic lines identified by chromosomes 2, 4, 6 and telosome 11 of the At subgenome and chromosomes 18 and 22 of the Dt subgenome, 22 monosomes were identified as duplicates of three monosomes (chromosomes 2, 4 and 6). Chromosome 4 of the At subgenome was recovered more frequently (18 times) than chromosome 2 of the At subgenome (4 times) and chromosome 6 of the At subgenome (3 times) during pollen irradiation at different doses and in the progeny of the desynaptic plants. These lines will be useful for molecular mapping and enhancement of Upland cotton.